Features of the new approach to solving the problem of detecting the integrity violations of digital images in various storage formats - Кобозєва, Алла Анатоліївна; Бобок, Іван Ігорович (Ukrainian Scientific Journal of Information Security, 2017)
At the moment, given the high level of development of computer technology, and information technology, the problem of quality checking the integrity, and development of effective methods of detecting the integrity violations of the digital images are very urgent. Existing methods do not provide a satisfactory solution to this problem, and often are focused on the specific storage format of the analyzed digital image. Recently, a new general approach to the organization of the examination the integrity violations of digital images was developed. Proposed approach is based on the analysis of singular numbers and singular vectors of blocks of their matrices, that obtained by standard partitioning. In this paper, we consider the features of the proposed approach depending on the storage format (lossy or losses) of the digital image. It is established that the main provisions of the approach are universal, regardless of the format of the analyzed image; the formal parameters of the images’ blocks stored in lossy are more sensitive to disturbing effects. The obtained results for the groups of corresponding digital images in various formats (lossy or losses) can be used to develop a method for detecting CIs that have been re-saved from lossy format to lossless format, which is relevant for the process of performing a steganalysis.